Quality of root canal fillings using three gutta-percha obturation techniques - Edith Siu Shan Ho; Jeffrey Wen Wei Chang; Gary Shun Pan Cheung (Korean Academy of Conservative Dentistry, 2016)
Objectives The goal of this study was to compare the density of gutta-percha root fillings obturated with the following techniques: cold lateral (CL) compaction, ultrasonic lateral (UL) compaction, and warm vertical (WV) compaction. Materials and Methods Thirty-three extracted mandibular first molars, with two separate mesial canals in each, were selected. After instrumentation, the canals were stratified into three groups based on canal length and curvature, and underwent obturation with one of the techniques. No sealer was used in order to avoid masking any voids. The teeth were imaged pre- and post-obturation using micro-computed tomography. The reconstructed three-dimensional images were analyzed volumetrically to determine the amount of gutta-percha present in every 2 mm segment of the canal. P values < 0.05 were considered to indicate statistical significance. Results The overall mean volume fraction of gutta-percha was 68.51 ± 6.75% for CL, 86.56 ± 5.00% for UL, and 88.91 ± 5.16% for WV. Significant differences were found between CL and UL and between CL and WV (p < 0.05), but not between UL and WV (p = 0.526). The gutta-percha density of the roots treated with WV and UL increased towards the coronal aspect, but this trend was not noted in the CL group. Conclusions WV compaction and UL compaction produced a significantly denser gutta-percha root filling than CL compaction. The density of gutta-percha was observed to increase towards the coronal aspect when the former two techniques were used.